Epidemiology of Hospital Onset Staphylococcus aureus Bloodstream Infections (HO-SA-BSI) in the Era of MRSA LabID Reporting. (October 2020) - Salgado, Cassandra; O'Driscoll, Stephanie; Puri, Shruti; Lorek, Adrienne; Curry, Scott
Abstract : Background: Acute-care hospitals began reporting methicillin-resistant Staphylococcus aureus (MRSA) LabID facility-wide inpatient events to the NHSN in 2013. Few data are available regarding the epidemiology of these patients. Methods: We conducted a retrospective cohort study of patients who developed hospital onset Staphylococcus aureus bloodstream infections (HO-SA-BSIs) to describe the epidemiology (characteristics and outcomes) from January 2014 through June 2019 and to compare MRSA LabID BSIs to HO-MSSA BSIs. Proportions were compared using 2 and continuous variables using the Kruskal-Wallis test (EpiInfo). Results: Overall, 264 HO-SA BSIs occurred over the study period (2.21 per 10, 000 patient days), 160 HO-MSSA BSIs (1.34 per 10, 000 patient days), and 104 MRSA LabID BSIs (0.869 per 10, 000 patient days). These rates have not significantly changed over time (Fig. 1). Most of these patients were men (64%); 42.4% were African-American; mean age was 43.5 years; mean Charlson comorbidity index was 3.2; 67.8% were admitted for medical care (vs surgical); and 13.3% had a previous history of S. aureus infection. Of all HO-SA-BSIs, 49.2% were acquired in the ICU, 53.8% were primary BSIs, and 37.9% were catheter associated. Patients were hospitalized a mean of 19.9 days prior to HO-SA BSI, and the mean overall length of stay was 48.5 days. Compared to HO-MSSA BSIs, there were no significant differences in these characteristics among MRSA LabID BSIs except that a significantly greater proportion were catheter associated (46.2% vs 32.5%; OR, 1.78; 95% CI, 1.07–2.96; P = .04). Overall, 101 patients (38.3%) died: 41 with MRSA LabID BSI (39.4%) and 60 with HO-MSSA BSI (37.5%). Mortality rates have not changed significantly over time. The mean number of days to death was 154.2, and 59 patients (22.3%) died during incident hospitalization: 26.9% of MRSA patients and 19.4% of MSSA BSI patients. Moreover, 28.3% of patients were readmitted within 30 days of discharge from incident hospitalization, and compared to HO-MSSA BSI, this rate was significantly higher among MRSA LabID BSI patients (34.2% vs 24.8%; OR, 2.07; 95% CI, 1.09–3.93; P = .03). Among those who died, 58.4% died during hospitalization, 52.5% died within 30 days, 66.3% died within 60 days, and 74.3% had died within 90 days. Also, 47.5% died as a result of their HO-SA BSI, and compared to HO-MSSA BSI, this rate was significantly higher among those with MRSA LabID-BSI (63.4% vs 36.7%; OR, 2.99; 95% CI, 1.31–6.83; P = .02). Conclusions: Among patients with HO-SA BSI, methicillin-resistance continues to be associated with higher attributable mortality, and in our study, higher rates of 30-day readmission. There has been no significant change in HO-SA BSI rates (MSSA or MRSA) since reporting for MRSA LabID events began. Furthermore, mortality rates have not changed and remain high for both MRSA BSI and MSSA BSI patients. Given these findings, MSSA LabID event reporting should be considered. Funding: None Disclosures: None